2015
DOI: 10.1093/bja/aeu402
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane promotes the expansion of glioma stem cells through activation of hypoxia-inducible factors in vitro

Abstract: Sevoflurane can promote the expansion of human GSCs through HIFs in vitro. Inhaled anaesthetics may enhance tumour growth through tumour stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 29 publications
1
48
0
1
Order By: Relevance
“…34 Sevoflurane has also been reported to promote expansion of glioma stem cells through activation of HIFs. 35 In concordance with these findings, we found in vitro migration of U251-GSCs pre-exposed in vivo to isoflurane was significantly greater and the migrated distance was increased.…”
Section: Discussionsupporting
confidence: 88%
“…34 Sevoflurane has also been reported to promote expansion of glioma stem cells through activation of HIFs. 35 In concordance with these findings, we found in vitro migration of U251-GSCs pre-exposed in vivo to isoflurane was significantly greater and the migrated distance was increased.…”
Section: Discussionsupporting
confidence: 88%
“…These results indicated that the inhibiting effects of sevoflurane on hypoxia-induced growth and metastasis of lung cancer cells might be through down-regulating HIF-1α protein level. However, sevoflurane has been reported to promote the expansion of glioma stem cells under normoxic conditions by up-regulating HIF-1α [22]. Sun et al found that sevoflurane preconditioning produces protective effects on survival and migration of bone marrow mesenchymal stem cells against hypoxia by up-regulating HIF-1α [23].…”
Section: Discussionmentioning
confidence: 99%
“…Pathway inhibitors (labeled in red) include PD98059, wortmannin, LY294002, and the tumor suppressor PTEN (Color figure online) the key involvement of PI3K, ERK 1/2, mitochondrial ATP-potassium channels, and mitochondrial permeability transition pore (mPTP) in reducing myocardial infarct size and myocyte apoptosis during early reperfusion by sevoflurane postconditioning. There has also been a recent report of sevoflurane-induced expansion of human glioma stem cells, with corresponding rises in HIF-1a, HIF-2a, p-AKT, and VEGF [50].…”
Section: Inhalational Anesthetics Hifs and Upstream Cell Signaling mentioning
confidence: 92%
“…Similarly, sevoflurane exposure enhanced proliferation of glioma stem cells, a finding which was reversed by the administration of small interfering RNA against HIFs [50].…”
Section: Cell Proliferationmentioning
confidence: 96%